TERTIARY PALAEOGEOGRAPHY AND TECTONOSTRATIGRAPHIC EVOLUTION OF THE NORTHERN AND SOUTHERN PERI-TETHYS PLATFORMS AND THE INTERMEDIATE DOMAINS OF THE AFRICAN-EURASIAN CONVERGENT PLATE BOUNDARY ZONE - Meulenkamp J.E.; Sissingh W. (My University, 2003)
The increasing effects of African–Eurasian convergence during the Tertiary resulted in the uplift and emergence of the Northern and Southern Peri-Tethys platforms. Palaeogeographic maps covering six selected time slices, including the Middle Eocene, late Early Oligocene, late Early Miocene, early Middle Miocene, early Late Miocene and Middle to Late Pliocene illustrate that environmental and depositional differentiations on the northern platform and along the bordering domains of the convergence zone were more pronounced than on the southern platform and its adjacent areas. The tectonic evolution of the northern platform included an overall eastward-directed trend in the onset of basin uplift and emergence, which started at about the Eocene–Oligocene transition, at 34 Ma. Tectonostratigraphic analyses indicate a striking contemporaneity of the events which defined the temporal and spatial development of both the domains of the convergent plate boundary zone and the bordering platforms. Five episodes of major regional change in palaeogeographic and tectonic setting are distinguished. They occurred in the Late Eocene (37–34 Ma), early Late Oligocene (30–27 Ma), latest Early to earliest Middle Miocene (17–15 Ma), early Late Miocene (9–8 Ma) and late Early to early Middle Pliocene (4–3 Ma). These episodes encompassed changes which were most probably induced by geodynamic events primarily related to the relative motions of the African/Arabian and Eurasian plates. In turn, the plate motions are assumed to have ‘triggered’ discrete steps in the regional kinematics and geodynamics that governed the palaeogeographic evolution of the Peri-Tethys platforms and the intermediate domains of the African–Eurasian plate boundary zone.
Keywords: palaeogeography; Tertiary; Europe; Mediterranean; North Africa; Middle East; Western/Central Asia; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene